Jobs, crime, and votes: A short-run evaluation of the refugee crisis in Germany - Markus Gehrsitz; Martin Ungerer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Millions of refugees made their way to Europe between 2014 and 2015, with over one million arriving in Germany alone. Yet, little is known about the impact of this inflow on labor markets, crime, and voting behavior. This article uses administrative data on refugee allocation and provides an evaluation of the short-run consequences of the refugee in ow. Our identification strategy exploits that a scramble for accommodation determined the assignment of refugees to German counties resulting in exogeneous variations in the number of refugees per county within and across states. Our estimates suggest that migrants have not displaced native workers but have themselves struggled to find gainful employment. We find moderate increases in crime and our analysis further indicates that while at the macro level increased migration was accompanied by increased support for anti-immigrant parties, exposure to refugees at the micro-level had the opposite effect.
Keywords: J6; J15; K4; D72; 330; Immigration; Refugees; Unemployment; Crime; Voting